Microwave-Assisted Synthesis of Phenothiazine and Quinoline Derivatives - Găină, Luiza (Molecular Diversity Preservation International (MDPI), 2007)
Application of a dynamic microwave power system in the chemical synthesis of some phenothiazine and quinoline derivatives is described. Heterocyclic ring formation, aromatic nucleophilic substitution and heterocyclic aldehydes/ketones condensation reactions were performed on solid support, or under solvent free reaction conditions. The microwave-assisted Duff formylation of phenothiazine was achieved. Comparison of microwave-assisted synthesis with the conventional synthetic methods demonstrates advantages related to shorter reaction times and in some cases better reaction yields.